Sustainable Tourism Development In The Context Of Regional Development At Ponot Waterfall, Asahan Regency - Gerry Pramudito, Mahendra; Negara Lubis, Satia; Sabrina, T. (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This Ponot Waterfall tour is located in Tangga Village, Aek Songsongan Regency, Asahan Regency, close to the Sigura-gura Dam and Rafting Tour which is an international event. The objectives of this study are (1) to analyze the strategy for developing sustainable tourism at Ponot Waterfall in Asahan Regency; and (2) analyzing the utilization of sustainable tourism development at Ponot Waterfall in the framework of regional development in Asahan Regency. The research method used is descriptive qualitative using SWOT analysis. Determination of informants using Purposive Sampling method. Data in this study were collected by interview, observation and document observation techniques. The results of this study are (1) the government needs to increase the development of Ponot Waterfall as a leading sustainabledestination in Asahan Regency. (2) the importance of paying attention to the utilization of Ponot Waterfall from an economic, social and cultural perspective for the surrounding community. Thus, it is expected to increase tourist visits to Ponot Waterfall and improve the welfare of the Asahan community as a whole